Does a run/walk strategy decrease cardiac stress during a marathon in non-elite runners?. Issue 1 (January 2016) - Hottenrott, Kuno; Ludyga, Sebastian; Schulze, Stephan; Gronwald, Thomas; Jäger, Frank-Stephan
Abstract: Objectives: Although alternating run/walk-periods are often recommended to novice runners, it is unclear, if this particular pacing strategy reduces the cardiovascular stress during prolonged exercise. Therefore, the aim of the study was to compare the effects of two different running strategies on selected cardiac biomarkers as well as marathon performance. Design: Randomized experimental trial in a repeated measure design. Methods: Male ( n  = 22) and female subjects ( n  = 20) completed a marathon either with a run/walk strategy or running only. Immediately after crossing the finishing line cardiac biomarkers were assessed in blood taken from the cubital vein. Before (−7 days) and after the marathon (+4 days) subjects also completed an incremental treadmill test. Results: Despite different pacing strategies, run/walk strategy and running only finished the marathon with similar times (04:14:25 ± 00:19:51 vs 04:07:40 ± 00:27:15 [hh:mm:ss]; p  = 0.377). In both groups, prolonged exercise led to increased B-type natriuretic peptide, creatine kinase MB isoenzyme and myoglobin levels ( p  < 0.001), which returned to baseline 4 days after the marathon. Elevated cTnI concentrations were observable in only two subjects. B-type natriuretic peptide ( r  = −0.363; p  = 0.041) and myoglobin levels ( r  = −0.456; p  = 0.009) were inversely correlated with the velocity at the individual anaerobic threshold. Run/walk strategy compared to running only reported less muscle pain and fatigue ( p  = 0.006) after the running event. Conclusions: In conclusion, the increase in cardiac biomarkers is a reversible, physiological response to strenuous exercise, indicating temporary stress on the myocyte and skeletal muscle. Although a combined run/walk strategy does not reduce the load on the cardiovascular system, it allows non-elite runners to achieve similar finish times with less (muscle) discomfort.